Immanuel Kant Application when army participates in Corona Virus Disease Prevention 2019 - Tomy Michael, (Technium Social Sciences Journal, 2021)
The type of research used in this study is a normative juridical legal research method. In answering the formulation of the problem, the answers obtained have a correlation with Immanuel Kant, especially the inclusion of the INA in Instruction No. 15-2021 is the opposite. This means that the existence of the INA will make the public as legal objects that are protected not because they have the right to get protection but rather lead to a reduction in rights. However, this correlation has contradictions about the duty of the army, which is actually protecting the country, not from enemies like the essence of the INA. This has also resulted in the task of the police being unclear due to the distribution of authority that isn’t in accordance with the law. As a way out, Instruction No. 15-2021 becomes a lesson and the emergence of other instructions doesn’t include INA.